Using collaborative strategic reading (CSR) to enhance achievement in reading comprehension of students with learning disabilities in Lagos State, Nigeria (2013)
This study determined the effect of Collaborative Strategic Reading (CSR) on enhancing the achievement in reading comprehension of students with learning disabilities in Lagos State, Nigeria. The pre-test, post-test, control group, quasi-experimental research design with a 2x2 factorial matrix was adopted for this study. Fifty junior secondary class 2 students with learning disabilities in reading were randomly selected from the sampled schools and randomized into two groups (Collaborative Strategic' Reading and control group). Two instruments were utilized namely, Pupil Rating Scale and Reading Comprehension Test. Participants in the experimental group were exposed to eight weeks training, while students in the control group were taught in the conventional way. Two hypotheses were tested at 0.05 level of significance. Data were analysed using analysis of variance and computation of t-test statistics. There was a significant main effect of treatment (Collaborative Strategic Reading) on the reading comprehension of students with learning disabilities (F (1.47) = 34.954; P<0.05). This implies that students exposed to Collaborative Strategic Reading performed better in reading comprehension than those exposed to Control Group. In addition, female participants performed better in the reading comprehension achievement test than their male counterparts (X= 21.69 for females and 15.75 for males). On the basis of these findings it was recommended that for schools to sustain improved achievement in reading comprehension among students with learning disabilities, Collaborative Strategic Reading should be adopted.